Memory-based multi-population genetic learning for dynamic shortest path problems - DIao, Yiya; Li, Changhe; Zeng, Sanyou; Mavrovouniotis, Michalis; Yang, Shengxiang (My University, 2019)
This paper proposes a general algorithm framework for solving dynamic sequence optimization problems (DSOPs). The framework adapts a novel genetic learning (GL) algorithm to dynamic environments via a clustering-based multi-population strategy with a memory scheme, namely, multi-population GL (MPGL). The framework is instantiated for a 3D dynamic shortest path problem, which is developed in this paper. Experimental comparison studies show that MPGL is able to quickly adapt to new environments and it outperforms several ant colony optimization variants.
Keywords: ant colony optimization; clusteringbased multi-population; dynamic sequence optimization; dynamic shortest path; genetic learning